Depiction of Dikpalas on the walls of the Antarala - Temples of India Project Team (Jio Institute, 2024)
Dikapalas (gods of cardinal directions) are also depicted on the walls of the antarala (vestibule or antechamber) of the Sitaleshwar Temple. One of the dikapalas is Varuna, depicted alongside his vahana (mount) Makara (crocodile-like sea creature). The ocean god is portrayed with two arms, holding a noose in his right hand and a water pitcher in his left.